“Bugabug ang dagat” (Rough seas): Experiencing Foucault’s heterotopia in fish trading houses - Turgo, Nelson N. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 8 No 1 (2012), 2012)
Places in the contemporary world are subjected to the workings of differentiating logics, foremost of which is globalization and to the other end, the counter-logic of localization, which results in, amongst others, the instantiation of differing spaces. These spaces, oftentimes co-existing and overlapping, are a result of contrapuntal forces, enacting their own colonization of places by people of varying interests. This article explores the other uses of kumisyunan (fish trading houses) by magririgaton (fish vendors) from a small fishing community in Quezon province that “simultaneously represent, contest, and invert” the very purpose and nature of the places’ rationale: fish trading. Heterotopia will be deployed in this article to further the ends of how a particular place could be inhabited by a number of spaces or exhibit alternate spatial possibilities and display a plethora of spatial practices within one singular location at different times in a particular spatial and temporal context. The article hopes to contribute to the further understanding of how everyday life and place is lived and reproduced in the variegated geographies of globalization in a developing economy like the Philippines. Keywords: auction, fishing community, fish trading, heterotopias, place, space